Industrial Revolution Technology 4.0: The Concept Of Blockchain Accounting To Detect Corruption In Government Public Sector Finance - Indira Nadya Ulya; Eva Rossiana Aulia Hidayah; Revilina Indah Sari (Jurnal Telekomunikasi dan Informatika, 2024)
The culture of corruption in the public sector of government is one of the cases that is still difficult to avoid until now. However, along with the development of industry 4.0, corruption cases can begin to be detected using current technology, one of which is blockchain technology. Blockchain technology can be combined with accounting so that it can detect corruption. This scientific work aims to provide a concept of blockchain performance in detecting corruption cases in the public sector of government. This research uses a literature review method of previous research which is then described using a qualitative approach. Blockchain public sector accounting is able to detect corruption because it uses a block recording system that is arranged with each other to form a chain and is permanent. If there is an invalid block, then there is data manipulation which can then be detected.